Evaluasi Kiprah Kaukus Lingkungan Hidup Anggota DPRD dalam Pengarusutamaan Lingkungan Hidup - Tjahjo Suprajogo (JIANA ( Jurnal Ilmu Administrasi Negara ), 2011)
DPRD (The House of Local People’s Representatives) as an legislative institution hasthe most important role in making the public policies. For strengthening the role of DPRD inenvironment mainstream so the caucus of DPRD was shaped. Through caucus channels, beprovided that many problems of environment getting the very serious concern from DPRD withusing their authoritative functions such as legislation, budgeting and controlling. The aims of thisresearch are evaluating how the role of caucus of DPRD and identifying supporting and inhibitingfactors of caucus role and recommendation for DPRD’s caucus in mainstreaming environment.This research using descriptive-qualitative method with purposive sampling. Depth interview anddocumentation as tehnique of gathering data. Unit of analysis in this research is environmentcaucus of DPRD at some regencies/municipalities of West Java Province and especially DPRD ofBandung municipality. The result of this research found that the caucus have tried to achieve thetargets in optimum although the caucus has to still work harder for actualizing green party, greenpolitician, green parlement, green policy and green budgeting and even green government. Theimplication of this research, there is the new paradigm in public policy study that based onmainstreaming environment. Further, it can be called Eco-Policy Study.